Investigation of the distribution of tension in notched construction elements - Neuber, H.; United States. Air Force. Systems Command. Aeronautical Systems Division. Directorate of Materials and Processesd States; Technische Hochschule München (Wright-Patterson Air Force Base, Ohio : Directorate of Materials and Processes, Aeronautical Systems Division, Air Force Systems Command, United States Air Force, 1963)
A new treatment of stress- and strain concentrations for special non-linear deformation law for shear is presented. A relation is obtained by which the real notch stress can be evaluated from the nominal stress and the elastic stress concentration factor. Static and fatigue tests are given for variously notched specimens. The strain-measurements were performed by electrical strain gages; additional measurements were made by means of the photoelastic stress-coat method. The aim of the static tests was die investiga tion of the notch-angle influence on the elastic stress concentration factor for tension and bend ing, the determination of the stress- and strain distribution in the elastic and plastic range respectively, and also the dependence of the stress concentration factor on the nominal stress for the materials used (Steel St.00.12, St.00.21, Aluminum alloy Velodur). The result of the fatigue tests was the establishment of Wohler curves for two different specimen shapes (bars with central holes) and their comparison with the Wohler-curve of the corresponding unnotched specimen.
"(Prepared under Contract No. AF 61(052)-200 by the Technische Hochschule, Munchen, Germany."
"Project No. 73561, Task No. 735106."
"May 1963."
Includes bibliographical references (page 16).
Mode of access: Internet.
will digitize
Keywords: Metals -- Fatigue; Steel alloys; Aluminum alloys; Strains and stresses